(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
Vehicular Adhoc Networks are of major interest of researchers nowadays. Despite of the huge attention of the researchers towards VANETs, there are still many issues regarding security of VANETs. Researchers are still going to secure the VANETS from different types of attacks and adversaries. There is a strong link between reliable network and security and privacy features. This paper provides a survey of problems in wireless networks like jamming attacks and their impact on the network. Many security issues are analyzed and have been discussed. Many researches about the solutions of the security attacks to the wireless networks have also been sum up in this paper.